Shakespeare on the Montreal Stage 1805-1826 - Ripley, John (Theatre Research in Canada / Recherches théâtrales au Canada, 1982)
A history and chronological bandlist of Shakespearian performances staged in Montreal between the construction of the city’s first permanent theatre space in 1804 and the conclusion of Edmund Kean’s visit in 1826. Some eighty performances included productions, readings, and adaptations of a dozen plays by such actors as the Allen-Bentley-Moore company, Seth Prigmore, Noble Luke Usher, Joseph Harper, Mr and Mrs John Mills, Frederick Brown, Emmanuel Judah, Robert Campbell Maywood, Lydia Kelly, Edmund Kean and Mrs Barnes. Un manuel et une liste écrite des représentations shakespeariennes montées à Montréal entre la construction de la première place du théâtre permanent en 1804 et de la fin de la visite de Edmund Kean en 1826. Environ quatre-vingts spectacles comprenaient des productions, des lectures, des adaptations d’une douzaine de pièces données par des acteurs de la compagnie Allen-Bentley-Moore, et par des personnes telles que Seth Prigmore, Noble Luke Usher, Joseph Harper, M et Madame John Mills, Frederick Brown, Emmanuel Judah, Robert Campbell Maywood, Lydia Kelly, Edmund Kean et Madame Barnes.